2021
DOI: 10.3390/ijms22073570
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/Valsartan Improves Diastolic Function But Not Skeletal Muscle Function in a Rat Model of HFpEF

Abstract: The angiotensin receptor/neprilysin inhibitor Sacubitril/Valsartan (Sac/Val) has been shown to be beneficial in patients suffering from heart failure with reduced ejection fraction (HFrEF). However, the impact of Sac/Val in patients presenting with heart failure with preserved ejection fraction (HFpEF) is not yet clearly resolved. The present study aimed to reveal the influence of the drug on the functionality of the myocardium, the skeletal muscle, and the vasculature in a rat model of HFpEF. Female obese ZSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 45 publications
4
36
0
Order By: Relevance
“…The observed effects on myocardial and SKM function are probably independent of modulating hypertension and glucose concentration ( Table 1). This in accordance with an earlier study by our group were the application of Sacubitril/Valsartan to ZSF1‐obese animals lowered blood pressure but had no effect on SKM atrophy/function 24 . Also, in a separate mouse study, we found that MyoMed‐205 had no significant effects on basal glucose or oral glucose tolerance 45 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed effects on myocardial and SKM function are probably independent of modulating hypertension and glucose concentration ( Table 1). This in accordance with an earlier study by our group were the application of Sacubitril/Valsartan to ZSF1‐obese animals lowered blood pressure but had no effect on SKM atrophy/function 24 . Also, in a separate mouse study, we found that MyoMed‐205 had no significant effects on basal glucose or oral glucose tolerance 45 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we tested if this compound class can also prevent SKM atrophy in HFpEF. For this, we selected the ZSF1 rat model that is commonly used to investigate interventional strategies in HFpEF 3,24,25 . As compound, we selected MyoMed‐205 that has improved serum stability when compared with initial lead compound ID#704946 21,22 (see Supporting Information, Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Sacubitril/Valsartan (LCZ696) is a new superstar in the management of heart failure and hypertension. Two recently-released independent studies showed that sacubitril/valsartan inhibits the progress of diastolic dysfunction and arterial stiffness to HFpEF in rat models ( 44 , 45 ). However, clinical trials are needed to verify the effects of sacubitril/valsartan on HFpEF patients.…”
Section: Does Treatment For Arterial Stiffness Benefit In Hfpef?mentioning
confidence: 99%
“…Obese diabetic Zucker fatty/spontaneously hypertensive HF F1 hybrid (ZSF1-OB) rats exhibit spontaneous type 2 diabetes, diabetic kidney disease, hypertension, hyperlipidemia, obesity and metabolic syndrome features ( Hohendanner et al, 2018 ; Davila et al, 2019 ; Leite et al, 2019 ; Park et al, 2020 ; Schauer et al, 2020 ). A number of studies demonstrated that ZSF1-OB had cardiac manifestations such as normal LVEF, increased E/A, left atrial enlargement, elevated LVEDP, upward EDPVR curve, and reduced activity tolerance ( Leite et al, 2019 ; Satoh et al, 2021 ; Schauer et al, 2021 ). In addition, compared with lean ZSF1(ZSF1-LN) in the control group, ZSF1-OB displayed significant aortic remodeling and arterial collagen deposition, central vascular remodeling, which aggravated the hypertensive phenotype and promoted HFpEF.…”
Section: Small Animal Models Of Hfpefmentioning
confidence: 99%